Dealing with lung cancer complications: how aggressive can we be? - How, Soon Hin (2013)
In Malaysia, lung cancer is the most common cancer (16.3%) among men and third most common cancer among women (5.4%, 2007 data) 1. It accounted for the most cancer deaths in 2001 that occurred in this country2. Most of our patients presented with advanced disease and surgery is not an option, more so, more than half of operable patients refused surgery 3. Hooi et al showed that operative rate for lung cancer was only 4.8% in Penang. 4Chemotherapy with or without radiotherapy is the treatment of choice in this group of patients 5. TKI is effective in EGFR mutation patient but it is not freely available to the poor. Despite recent advancement in the treatment of lung cancer, most of our advanced lung cancer patients suffered from various complications including SVC or airway obstruction, dyspnea due to pleural or pericardial effusion, lymphagitis carcinomatosis, distance metastasis to brain, spine, bone etc, haemoptysis and paraneoplastic syndrome. We should be familiar and aggressive in managing their complications in order to prolong their life.